A high-strength antibacterial PETG material, preparation method and medical packaging application

By introducing modified composite antibacterial agents and functional additives into PETG materials, high-strength antibacterial PETG materials are formed, which solves the problems of insufficient antibacterial properties and antibacterial agent precipitation of PETG materials in the medical packaging field, and achieves excellent antibacterial, mechanical and aging resistance.

CN118813058BActive Publication Date: 2025-03-25DONG GUAN WANSUCHENG PLASTIC CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410901863.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2025-03-25
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

Due to the lack of antibacterial properties in the fields of medical packaging and cosmetic packaging, PETG materials are prone to spilling small molecule raw materials, causing mold problems. The addition of existing antibacterial agents has problems such as precipitation, segregation, decreased mechanical properties and reduced aging resistance.

Method used

Using high-strength antibacterial PETG material, a material with excellent antibacterial properties, good mechanical properties and aging resistance is prepared by combining modified PETG and modified composite antibacterial agents and functional additives. Modified composite antibacterial agents fix antibacterial agents by forming microsphere structures to avoid precipitation and performance reduction.

Benefits of technology

The excellent antibacterial properties, mechanical properties and aging resistance of PETG materials in the medical packaging field are achieved, avoiding the precipitation and performance reduction of antibacterial agents, and improving the stability and use efficiency of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004930684540000141
    Figure BDA0004930684540000141
Patent Text Reader

Abstract

The present application relates to the field of polymer materials, and in particular to a high-strength antibacterial PETG material, a preparation method, and medical packaging applications. The high-strength antibacterial PETG material, in parts by mass, comprises raw materials including: 80 to 100 parts of modified PETG, 0.5 to 10 parts of modified composite antibacterial agents, and 1 to 10 parts of functional additives. The PETG material prepared in the present application not only has excellent antibacterial properties, but also has good mechanical properties and aging resistance, avoiding the technical problems of precipitation and performance degradation caused by the addition of antibacterial agents in the past, improving its use efficacy in the field of medical packaging, and has excellent market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polymer materials, and in particular to a high-strength antibacterial PETG material, a preparation method and medical packaging applications. Background Art

[0002] PETG material is a transparent non-crystalline copolyester plastic, and its full name is polyethylene terephthalate-1,4-cyclohexanedimethanol. PETG material has excellent adhesion, transparency, hue, chemical resistance, and stress whitening resistance, and it has excellent processing and forming properties during processing and use. Therefore, it can be processed by extrusion, injection molding, blow molding, and vacuum forming. It is an excellent processable polymer material and is widely used in the fields of plates, sheets, films, and profiles.

[0003] The hot application of PETG materials has gradually penetrated into the field of packaging materials, especially for the balance control of packaging cost and packaging performance. However, at the same time, some defects of PETG materials themselves have also significantly limited its scope of application. For example, in the field of medical packaging and cosmetic packaging, since PETG materials themselves do not have antibacterial properties, small molecule raw materials will overflow on the surface when used in the above packaging, which is prone to mold. For the above problems, the existing solution is to add some antibacterial agents to solve the mold problem, but the addition of antibacterial agents still has problems such as precipitation, segregation, decreased mechanical properties and reduced aging resistance.

[0004] Therefore, in order to solve the above problems, the present application provides a high-strength antibacterial PETG material and a preparation method. The PETG material prepared in the present application not only has excellent antibacterial properties, but also has good mechanical properties and aging resistance, thereby avoiding the technical problems of precipitation and performance degradation caused by the addition of antibacterial agents in the past, improving its use efficacy in the field of medical packaging, and having excellent market prospects. Summary of the invention

[0005] In order to solve the above problems, the first aspect of the present application provides a high-strength antibacterial PETG material. The raw materials include, by mass: 80 to 100 parts of modified PETG, 0.5 to 10 parts of modified composite antibacterial agent, and 1 to 10 parts of functional additives.

[0006] As a preferred solution, the mass ratio of the modified PETG to the modified composite antibacterial agent is (85-95):(4-8).

[0007] As a preferred solution, the mass ratio of the modified PETG to the modified composite antibacterial agent is (88-92): (5.5-7.5).

[0008] As a preferred scheme, the preparation method of the modified PETG comprises the following steps: S1: mixing terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydroxypolydimethylsiloxane and adding a catalyst, heating to 250-280°C, controlling the pressure to 240-260KPa and reacting for 2-3h to obtain product A; S2: mixing terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydrogenated bisphenol F and adding a catalyst, heating to 260-280°C, controlling the pressure to 260-290KPa and reacting for 2-3h to obtain product B; S3: mixing product A and product B, adding a catalyst, heating to 260-290°C, maintaining a vacuum degree of -0.096MPa and reacting for 3-4h, and obtaining modified PETG after completion.

[0009] As a preferred solution, in S1, the mass ratio of terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydroxypolydimethylsiloxane is (7-10): (3-5): (2-4): (0.5-1.5).

[0010] As a preferred solution, in S1, the mass ratio of terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydroxypolydimethylsiloxane is (8-9): (3-4): (2-3): (1-1.2).

[0011] As a preferred solution, in S2, the mass ratio of terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydrogenated bisphenol F is (6-8):(2-3):(5-6):(2-3).

[0012] As a preferred solution, in S2, the mass ratio of terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydrogenated bisphenol F is (6.5-7): (2-2.5): 5.5:2.

[0013] As a preferred solution, the mass ratio of the product A to the product B is (1-2): (1.5-2.5).

[0014] As a preferred solution, the catalyst is at least one of tetrabutyl titanate, zirconate, p-toluenesulfonic acid, and boron trifluoride.

[0015] As a preferred solution, the catalyst is tetrabutyl titanate.

[0016] The modified PETG material used in the present application can effectively improve its mechanical properties while further ensuring excellent aging resistance, and avoids the precipitation of small molecule raw materials in the system. Hydrogenated bisphenol F can provide a saturated cyclic structure in the modified PETG. The existence of this structure can provide a more stable structural support in the material system while improving the system's tolerance to thermal energy. The existence of the saturated cyclic structure avoids excessive reaction of active groups within the material system and gives the material surface a larger polymer matrix content, thereby forming an excellent and smooth low surface energy surface, thereby inhibiting the penetration of active groups and active molecules and their migration efficiency within the material under specific high light, high heat, high humidity and other environments, thereby obtaining excellent aging resistance stability; on the other hand, by introducing hydroxy polydimethylsiloxane molecular chains into the PETG material, a good block copolymer and graft copolymer structure can be formed, thereby forming a dense network structure formed by long chain entanglement with good performance in the system. The existence of this structure can not only provide good material stability and mechanical connection and support effects for the PETG material, but the unique hydrophobic end of the extended chain segment can help establish a surface waterproof permeation membrane layer, thereby greatly improving the waterproof effect.

[0017] As a preferred scheme, the preparation method of the modified composite antibacterial agent includes the following steps: S1: mixing zinc oxide, carboxylic acid and silane coupling agent in deionized water, heating to 60-65°C, stirring at 100-200r / min for reaction for 3-4h, and centrifuging and precipitating after completion to obtain pretreated zinc oxide; S2: mixing the pretreated zinc oxide and quaternary phosphonium salt into deionized water and mixing evenly, then adding zinc acetate and heating to 60-80°C for insulation for 1-2h; S3: adding methanol solution of dimethylimidazole dropwise to the S2 solution, the dropping temperature is 60-75°C, the dropping time is 1-2h, and after the dropping is completed, adding glutaric anhydride and continuously keeping warm and stirring for reaction for 2-3h, and after the reaction is completed, centrifuging and filtering, washing with ethanol and drying to obtain the product.

[0018] As a preferred solution, the average particle size of the zinc oxide is 10 to 30 nm.

[0019] As a preferred solution, the mass ratio of zinc oxide, carboxylic acid and silane coupling agent is (2-2.5): (1-3): (0.3-0.6).

[0020] As a preferred solution, the mass ratio of zinc oxide, carboxylic acid and silane coupling agent is 2: (2-2.2): (0.4-0.5).

[0021] As a preferred solution, the silane coupling agent is at least one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0022] As a preferred solution, the silane coupling agent is vinyltrimethoxysilane.

[0023] As a preferred solution, the mass ratio of the pretreated zinc oxide, quaternary phosphonium salt, zinc acetate and dimethylimidazole is (1-1.5): (1-1.5): (2-3): (4-5).

[0024] As a preferred solution, the mass ratio of the pretreated zinc oxide, quaternary phosphonium salt, zinc acetate and dimethylimidazole is (1.2-1.4): (1-1.2): 2.5: 4.5.

[0025] As a preferred solution, the quaternary phosphonium salt is at least one of dodecyltrimethylphosphonium chloride, dodecyltributylphosphonium chloride, dodecyltrimethylphosphonium bromide, dodecyltributylphosphonium bromide, dodecyltriphenylphosphonium chloride and dodecyltriphenylphosphonium bromide.

[0026] As a preferred solution, the quaternary phosphonium salt is dodecyltrimethylphosphonium bromide.

[0027] As a preferred solution, the amount of glutaric anhydride added is 3-5% of the total mass of the S3 reaction solution.

[0028] The modified composite antibacterial agent added in the present application can not only give the PETG material good antibacterial properties, but also further ensure the stability of the antibacterial agent in the PETG material system, thereby avoiding its precipitation or stratification phenomenon, and can effectively improve the mechanical and waterproof properties of the PETG material. The modified composite antibacterial agent can use the formed skeleton-supported microsphere structure as a fixed carrier of the quaternary phosphonium salt antibacterial agent, because the microsphere structure can use the multi-active hydroxyl, carboxyl and other groups on its surface to form a connection inside the PETG material, so when the material is prepared, it can stably fix the position of the antibacterial agent inside the PETG material, reduce its mobility, and then in a specific and complex environment, it can ensure the preservation effect of the antibacterial agent inside, thereby avoiding precipitation phenomenon; on the other hand, the formed microsphere structure not only has a good connection effect, but its skeleton structure can provide a good support site effect when the material is subjected to external force, thereby increasing the upper limit of the external force bearing of the material when the external force acts, and the presence of the microsphere structure is also conducive to the adsorption of bacteria and other organic pollutants, and through a certain light oxidation effect, it is oxidized, degraded and decomposed, thereby ensuring the neatness of the performance and improving the various properties of the material.

[0029] As a preferred solution, the functional additive is at least one of an antioxidant, a flame retardant, a water-repellent, a UV-resistant agent, a stabilizer, a dispersant, a lubricant, a thickener, and a toughening agent.

[0030] As a preferred solution, the functional additives are antioxidants, flame retardants and stabilizers.

[0031] As a preferred solution, the mass ratio of the antioxidant, flame retardant and stabilizer is (1-2): (5-6): (0.5-1.5).

[0032] As a preferred solution, the mass ratio of the antioxidant, flame retardant and stabilizer is (1-1.5): (5-6): (0.5-1).

[0033] As a preferred solution, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, antioxidant 168, and antioxidant 626.

[0034] As a preferred solution, the flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, zinc borate, phosphate ester and phosphite ester.

[0035] As a preferred solution, the stabilizer is calcium stearate or zinc stearate.

[0036] The second aspect of the present application provides a method for preparing the above-mentioned high-strength antibacterial PETG material, which comprises: mixing the modified PETG, the modified composite antibacterial agent and the functional additive in a high-speed mixer at 200 to 400 r / min for 2 to 3 hours, and obtaining the material after completion.

[0037] The third aspect of the present application provides an application of the above-mentioned high-strength antibacterial PETG material in medical packaging materials.

[0038] The beneficial effects of this application are:

[0039] 1. The high-strength antibacterial PETG material provided in the present application not only has excellent antibacterial properties, but also has good mechanical properties and aging resistance, thereby avoiding the technical problems of precipitation and performance degradation caused by the addition of antibacterial agents in the past, improving its use efficacy in the field of medical packaging, and having excellent market prospects.

[0040] 2. A high-strength antibacterial PETG material provided in the present application, wherein the added modified PETG material can effectively improve its mechanical properties while further ensuring excellent aging resistance, and avoid the precipitation of small molecule raw materials in the system; hydrogenated bisphenol F can provide a saturated cyclic structure in the modified PETG, and the presence of this structure can provide a more stable structural support in the material system while improving the system's tolerance to thermal energy, and the presence of the saturated cyclic structure avoids excessive reaction of active groups within the material system, and gives the material surface a higher content of polymer matrix, thereby forming an excellent and smooth low surface energy surface, thereby inhibiting the penetration of active groups and active molecules and their migration efficiency within the material under specific high light, high heat, high humidity and other environments, thereby obtaining excellent aging resistance stability.

[0041] 3. A high-strength antibacterial PETG material provided in the present application, the hydroxy polydimethylsiloxane molecular chain introduced in it can form a good block copolymer and graft copolymer structure, thereby forming a dense network structure formed by the entanglement of long chains with good performance in the system. The existence of this structure can not only provide good material stability and mechanical connection and support effects for the PETG material, but the unique hydrophobic end of the extended chain segment can help establish a surface waterproof penetration membrane layer, thereby greatly improving the waterproof effect.

[0042] 4. The high-strength antibacterial PETG material provided in the present application, the modified composite antibacterial agent added thereto can not only give the PETG material good antibacterial properties, but also can further ensure the stability of the antibacterial agent in the PETG material system, thereby avoiding its precipitation or stratification, and can effectively improve the mechanical and waterproof properties of the PETG material. DETAILED DESCRIPTION

[0043] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0044] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0045] Example 1

[0046] Embodiment 1 The first aspect provides a high-strength antibacterial PETG material, which comprises, by weight, 90 parts of modified PETG, 7 parts of modified composite antibacterial agent, and 8 parts of functional additive.

[0047] The preparation method of modified PETG comprises the following steps, calculated by mass: S1: 8.5 parts of terephthalic acid, 3.5 parts of 1,4-cyclohexanedimethanol, 2.6 parts of ethylene glycol and 1.1 parts of hydroxy polydimethylsiloxane are mixed and 0.02 parts of catalyst are added, the temperature is raised to 260°C, the pressure is controlled to 250KPa, and the reaction is carried out for 2.5 hours to obtain product A; S2: 6.5 parts of terephthalic acid, 2.2 parts of 1,4-cyclohexanedimethanol, 5.5 parts of ethylene glycol and 2 parts of hydrogenated bisphenol F are mixed and 0.02 parts of catalyst are added, the temperature is raised to 275°C, the pressure is controlled to 280KPa, and the reaction is carried out for 3 hours to obtain product B; S3: 1.5 parts of product A and 2 parts of product B are mixed, 0.01 parts of catalyst are added, the temperature is raised to 280°C, the vacuum degree is maintained at -0.096MPa, and the reaction is carried out for 3.5 hours, and the modified PETG is obtained after completion.

[0048] The catalyst is tetrabutyl titanate.

[0049] The preparation method of the modified composite antibacterial agent includes the following steps, calculated by mass: S1: 2 parts of zinc oxide, 2.2 parts of succinic acid and 0.45 parts of vinyltrimethoxysilane are mixed in 50 parts of deionized water, the temperature is raised to 65°C, and the reaction is stirred at a speed of 120r / min for 3 hours. After completion, the centrifugal precipitation is washed to obtain pretreated zinc oxide; S2: 1.2 parts of pretreated zinc oxide and 1 part of quaternary phosphonium salt are mixed and added to 30 parts of deionized water, and then 2.5 parts of zinc acetate are added and the temperature is raised to 75°C and kept warm for 2 hours; S3: A methanol solution containing 4.5 parts of dimethylimidazole (a total of 25 parts) is added dropwise to the S2 solution, the dropping temperature is 65°C, the dropping time is 2 hours, and after the dropwise addition is completed, glutaric anhydride is added and the reaction is continued for 3 hours of continuous stirring and keeping warm. After the reaction is completed, centrifugal filtration, ethanol washing and drying are performed.

[0050] The average particle size of zinc oxide is 20 nm.

[0051] The amount of glutaric anhydride added is 3.5% of the total mass of the S3 reaction solution.

[0052] The quaternary phosphonium salt is dodecyltrimethylphosphonium bromide.

[0053] The functional additives are antioxidant, flame retardant and stabilizer; the mass ratio of the antioxidant, flame retardant and stabilizer is 1:6:1.

[0054] The antioxidant is antioxidant 1076; the flame retardant is phosphite; and the stabilizer is calcium stearate.

[0055] The second aspect of this embodiment provides a method for preparing the above-mentioned high-strength antibacterial PETG material, the preparation method comprising: mixing the modified PETG, the modified composite antibacterial agent and the functional additive in a high-speed mixer at 360 r / min for 3 hours, and obtaining the material after completion.

[0056] Example 2

[0057] Embodiment 2 The first aspect provides a high-strength antibacterial PETG material, in parts by mass, the raw materials include: 95 parts of modified PETG, 5 parts of modified composite antibacterial agent, and 6.5 parts of functional additives.

[0058] The preparation method of modified PETG comprises the following steps, calculated by mass: S1: 8.5 parts of terephthalic acid, 3.5 parts of 1,4-cyclohexanedimethanol, 2.6 parts of ethylene glycol and 1.1 parts of hydroxy polydimethylsiloxane are mixed and 0.02 parts of catalyst are added, the temperature is raised to 260°C, the pressure is controlled to 250KPa, and the reaction is carried out for 2.5 hours to obtain product A; S2: 6.5 parts of terephthalic acid, 2.2 parts of 1,4-cyclohexanedimethanol, 5.5 parts of ethylene glycol and 2 parts of hydrogenated bisphenol F are mixed and 0.02 parts of catalyst are added, the temperature is raised to 275°C, the pressure is controlled to 280KPa, and the reaction is carried out for 3 hours to obtain product B; S3: 1.5 parts of product A and 2 parts of product B are mixed, 0.01 parts of catalyst are added, the temperature is raised to 280°C, the vacuum degree is maintained at -0.096MPa, and the reaction is carried out for 3.5 hours, and the modified PETG is obtained after completion.

[0059] The catalyst is tetrabutyl titanate.

[0060] The preparation method of the modified composite antibacterial agent includes the following steps, calculated by mass: S1: 2 parts of zinc oxide, 2.2 parts of succinic acid and 0.45 parts of vinyltrimethoxysilane are mixed in 50 parts of deionized water, the temperature is raised to 65°C, and the reaction is stirred at a speed of 120r / min for 3 hours. After completion, the centrifugal precipitation is washed to obtain pretreated zinc oxide; S2: 1.2 parts of pretreated zinc oxide and 1 part of quaternary phosphonium salt are mixed and added to 30 parts of deionized water, and then 2.5 parts of zinc acetate are added and the temperature is raised to 75°C and kept warm for 2 hours; S3: A methanol solution containing 4.5 parts of dimethylimidazole (a total of 25 parts) is added dropwise to the S2 solution, the dropping temperature is 65°C, the dropping time is 2 hours, and after the dropwise addition is completed, glutaric anhydride is added and the reaction is continued for 3 hours of continuous stirring and keeping warm. After the reaction is completed, centrifugal filtration, ethanol washing and drying are performed.

[0061] The average particle size of zinc oxide is 20 nm.

[0062] The amount of glutaric anhydride added is 4% of the total mass of the S3 reaction solution.

[0063] The quaternary phosphonium salt is dodecyltriphenylphosphonium chloride.

[0064] The functional additives are antioxidant, flame retardant and stabilizer; the mass ratio of the antioxidant, flame retardant and stabilizer is 1:5:0.5.

[0065] The antioxidant is antioxidant 1098; the flame retardant is aluminum hydroxide; and the stabilizer is zinc stearate.

[0066] The second aspect of this embodiment provides a method for preparing the above-mentioned high-strength antibacterial PETG material, the preparation method comprising: mixing the modified PETG, the modified composite antibacterial agent and the functional additive in a high-speed mixer at 360 r / min for 3 hours, and obtaining the material after completion.

[0067] Comparative Example 1

[0068] The specific implementation of this comparative example is basically the same as that of Example 1, except that the high-strength antibacterial PETG material, in parts by mass, includes: 100 parts of modified PETG, 2.5 parts of modified composite antibacterial agent, and 8 parts of functional additives.

[0069] Comparative Example 2

[0070] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified PETG comprises the following steps, by mass: S1: 8.5 parts of terephthalic acid, 3.5 parts of 1,4-cyclohexanedimethanol, 2.6 parts of ethylene glycol and 1.1 parts of hydroxy polydimethylsiloxane are mixed and 0.02 parts of catalyst are added, the temperature is raised to 260°C, the pressure is controlled at 250KPa, and the reaction is carried out for 2.5 hours to obtain product A; S2: 6.5 S3: Mix 0.45 parts of product A and 4.5 parts of product B, add 0.01 parts of catalyst, heat to 280°C, maintain vacuum degree -0.096MPa and react for 3.5h, and obtain modified PETG.

[0071] Comparative Example 3

[0072] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified PETG comprises the following steps, by mass: S1: 6.5 parts of terephthalic acid, 4.5 parts of 1,4-cyclohexanedimethanol, 3.6 parts of ethylene glycol and 0.4 parts of hydroxypolydimethylsiloxane are mixed and 0.02 parts of catalyst are added, the temperature is raised to 260°C, the pressure is controlled at 250KPa, and the reaction is carried out for 2.5 hours to obtain product A; S2: 6 .5 parts of terephthalic acid, 2.2 parts of 1,4-cyclohexanedimethanol, 5.5 parts of ethylene glycol and 2 parts of hydrogenated bisphenol F are mixed and 0.02 parts of catalyst are added, the temperature is raised to 275°C, the pressure is controlled at 280KPa and the reaction is carried out for 3 hours to obtain product B; S3: 1.5 parts of product A and 2 parts of product B are mixed, 0.01 parts of catalyst are added, the temperature is raised to 280°C, the vacuum degree is maintained at -0.096MPa and the reaction is carried out for 3.5 hours, and the modified PETG is obtained after completion.

[0073] Comparative Example 4

[0074] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified PETG comprises the following steps, by mass: S1: 8.5 parts of terephthalic acid, 3.5 parts of 1,4-cyclohexanedimethanol, 2.6 parts of ethylene glycol and 1.1 parts of hydroxy polydimethylsiloxane are mixed and 0.02 parts of catalyst are added, the temperature is raised to 260°C, the pressure is controlled at 250KPa, and the reaction is carried out for 2.5 hours to obtain product A; S2: 8 S3: Mix 1.5 parts of product A and 2 parts of product B, add 0.01 parts of catalyst, heat to 280°C, keep the vacuum degree at -0.096MPa and react for 3.5 hours, and then obtain modified PETG.

[0075] Comparative Example 5

[0076] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified composite antibacterial agent includes the following steps, measured in parts by mass: S1: 2 parts of zinc oxide, 2.2 parts of carboxylic acid and 0.45 parts of vinyltrimethoxysilane are mixed in 50 parts of deionized water, the temperature is raised to 65°C, and the reaction is stirred at a speed of 120r / min for 3 hours. After completion, the precipitation is centrifuged and washed to obtain pretreated zinc oxide; S2: 0.5 parts of pretreated zinc oxide and 2 parts of quaternary phosphonium salt are mixed and added to 30 parts of deionized water, and then 4.5 parts of zinc acetate are added and the temperature is raised to 75°C and kept warm for 2 hours; S3: 8.5 parts of methanol solution containing dimethylimidazole (25 parts in total) are added dropwise to the S2 solution, the dropping temperature is 65°C, the dropping time is 2 hours, and after the dropwise addition is completed, glutaric anhydride is added and the reaction is continued by stirring and keeping warm for 3 hours. After the reaction is completed, centrifugal filtration, ethanol washing and drying are performed.

[0077] Comparative Example 6

[0078] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified composite antibacterial agent includes the following steps, calculated by mass: S1: 2 parts of zinc oxide, 0.5 parts of carboxylic acid and 0.18 parts of vinyltrimethoxysilane are mixed in 50 parts of deionized water, the temperature is raised to 65°C, and the reaction is stirred at a speed of 120r / min for 3 hours. After completion, the centrifugal precipitation is washed to obtain pretreated zinc oxide; S2: 1.2 parts of pretreated zinc oxide and 1 part of quaternary phosphonium salt are mixed and added to 30 parts of deionized water, and then 2.5 parts of zinc acetate are added and the temperature is raised to 75°C and kept warm for 2 hours; S3: A methanol solution containing 4.5 parts of dimethylimidazole (a total of 25 parts) is added dropwise to the S2 solution, the dropping temperature is 65°C, the dropping time is 2 hours, and after the dropwise addition is completed, glutaric anhydride is added and the reaction is continued by stirring and keeping warm for 3 hours. After the reaction is completed, centrifugal filtration, ethanol washing and drying are performed.

[0079] Comparative Example 7

[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 50 nm.

[0081] Performance Evaluation

[0082] Antibacterial test: The antibacterial rate of the PETG material was obtained by testing the examples and comparative examples according to GB / T 31402-2015 standard. The test bacteria was Escherichia coli. The measured numerical results were the average of 10 tests and recorded in Table 1.

[0083] Waterproof performance: The PETG materials obtained in the embodiments and comparative examples were used to prepare samples with a size of 1 cm in length × 1 cm in width × 0.1 cm in thickness. The surface water contact angle was tested by the sessile drop method. The test drop size was 2 μL and the test time was 15 s. The measured numerical results were averaged from 10 tests and recorded in Table 1.

[0084] Impact strength: The impact strength of the PETG material was obtained by testing the examples and comparative examples according to GB / T 1043.1-2008 standard. The measured numerical results were recorded in Table 1 as the average value of 10 tests.

[0085] Aging resistance: The PETG materials obtained in the embodiments and comparative examples were placed in a constant temperature and humidity chamber, set at 65°C and 75% humidity for 28 days. After 28 days, the materials were taken out and their impact strength was retested. The impact strength retention rate was calculated as %, where impact strength retention rate % = impact strength after test / impact strength before test × 100%. The average value of the measured numerical results for 10 tests was recorded in Table 1.

[0086] Table 1 Performance test results

[0087]

[0088] From the data results of the embodiments and comparative examples of the present application and Table 1, it can be known that the embodiments 1 and 2 of the present application have obvious performance advantages in terms of antibacterial properties, mechanical properties, waterproof properties and aging resistance compared to comparative examples 1 to 7; this is because embodiments 1 and 2 adopt the technical solution defined in the present application, and introduce a saturated cyclic structure into the material system. The existence of this structure can provide a more stable structural support in the material system while improving the system's tolerance to thermal energy, and the existence of the saturated cyclic structure avoids the excessive reaction of the active group inside the material system, and gives the material surface a large amount of polymer matrix content, thereby forming an excellent and smooth low surface energy surface, thereby inhibiting the penetration of active groups and active molecules and their migration efficiency inside the material under specific high light, high heat, high humidity and other environments, and thus obtaining excellent aging resistance stability. Comparative examples 1 to 7 have a significant decline in performance because they do not adopt the correct technical solution, which further proves the importance of the technical solution defined in the present application to the technical effect of the present application.

Claims

1. A high-strength antibacterial PETG material, characterized in that: High-strength antibacterial PETG material, calculated by weight, the raw materials include: 80-100 parts of modified PETG, 0.5-10 parts of modified composite antibacterial agent, 1-10 parts of functional additives; The mass ratio of the modified PETG and the modified composite antibacterial agent is (85-95): (4-8); The preparation method of the modified PETG comprises the following steps: S1: mixing terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydroxy polydimethylsiloxane, adding a catalyst, heating to 250-280° C., controlling the pressure to 240-260 KPa, reacting for 2-3 hours, and obtaining product A; S2: mixing terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydrogenated bisphenol F, adding a catalyst, heating to 260-280° C., controlling the pressure to 260-290 KPa, and reacting for 2-3 hours, and obtaining product B; S3: mixing product A and product B, adding a catalyst, heating to 260-290° C., maintaining a vacuum degree of -0.096 MPa, and reacting for 3-4 hours, and obtaining modified PETG after completion; In S1, the mass ratio of terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydroxypolydimethylsiloxane is (7-10): (3-5): (2-4): (0.5-1.5); In S2, the mass ratio of terephthalic acid, 1,4-cyclohexanedimethanol, ethylene glycol and hydrogenated bisphenol F is (6-8):(2-3):(5-6):(2-3); The mass ratio of the product A to the product B is (1-2): (1.5-2.5); The catalyst is at least one of tetrabutyl titanate, zirconate, p-toluenesulfonic acid, and boron trifluoride; The preparation method of the modified composite antibacterial agent comprises the following steps: S1: mixing zinc oxide, carboxylic acid and silane coupling agent in deionized water, heating to 60-65°C, stirring at a speed of 100-200 r / min for reaction for 3-4 hours, and centrifuging and precipitating after completion to obtain pretreated zinc oxide; S2: mixing the pretreated zinc oxide and quaternary phosphonium salt, adding them to deionized water and mixing them evenly, then adding zinc acetate, heating to 60-80°C and keeping warm for 1-2 hours; S3: adding methanol solution of dimethylimidazole dropwise to the S2 solution, the dropping temperature is 60-75°C, the dropping time is 1-2 hours, adding glutaric anhydride after the dropping is completed, and continuing to keep warm and stir for reaction for 2-3 hours, and after the reaction is completed, centrifuging and filtering, washing with ethanol and drying to obtain the modified composite antibacterial agent.

2. The high-strength antibacterial PETG material according to claim 1, characterized in that: The mass ratio of the zinc oxide, carboxylic acid and silane coupling agent is (2-2.5): (1-3): (0.3-0.6).

3. The high-strength antibacterial PETG material according to claim 2, characterized in that: The silane coupling agent is at least one of γ-aminopropyltriethoxysilane, vinyltriethoxysilane and vinyltrimethoxysilane.

4. The high-strength antibacterial PETG material according to claim 3, characterized in that: The mass ratio of the pretreated zinc oxide, quaternary phosphonium salt, zinc acetate and dimethylimidazole is (1-1.5): (1-1.5): (2-3): (4-5).

5. The high-strength antibacterial PETG material according to claim 4, characterized in that: The quaternary phosphonium salt is at least one of dodecyltrimethylphosphonium chloride, dodecyltributylphosphonium chloride, dodecyltrimethylphosphonium bromide, dodecyltributylphosphonium bromide, dodecyltriphenylphosphonium chloride and dodecyltriphenylphosphonium bromide.

6. The high-strength antibacterial PETG material according to claim 5, characterized in that: The functional additive is at least one of an antioxidant, a flame retardant, a water-proofing agent, an ultraviolet resistant agent, a stabilizer, a dispersant, a lubricant, a thickener, and a toughening agent.

7. The high-strength antibacterial PETG material according to claim 6, characterized in that: The functional additives are antioxidants, flame retardants and stabilizers; the mass ratio of the antioxidants, flame retardants and stabilizers is (1-2): (5-6): (0.5-1.5).

8. A method for preparing the high-strength antibacterial PETG material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: mixing the modified PETG, the modified composite antibacterial agent and the functional additive in a high-speed mixer at a high speed of 200-400 r / min for 2-3 hours, and obtaining the product after completion.

9. Use of the high-strength antibacterial PETG material according to any one of claims 1 to 7 in medical packaging materials.

Citation Information

Patent Citations

  • Organosilicone copolyester

    CN103304795A

  • High-temperature resistant modified copolyester

    CN109929096A